(untitled) (International Journal of Physiotherapy, 2015)
Background: Acupuncture is an component of traditional Chinese medicine (TCM) that has been used for three thousand years to treat diseases and relieve pain. Pain is found to be the most common reason for people to use acupuncture. Due to recent scientific findings, acupuncture treatment has been accepted worldwide. Numerous trials have been conducted especially in analgesia. The mechanisms of acupuncture analgesia has been widely investigated, however, the underlying mechanism still not clear. This article summarizes the central mechanisms of acupuncture analgesia and reviews recent studies on the topic. Method: We have focused on examining the recent literature on acupuncture analgesia. The central mechanisms of acupuncture analgesia and reviews recent studies on the topic. We focused on the studies related to central mechanisms of acupuncture analgesia from these aspects: (neurophysiology, neurochemistry and neuroanatomy). Result: The result revealed that acupuncture act on various parts of the central nervous system, including the spinal cord, brain stem, cerebral ganglia and cerebral cortex to alleviate pain. The central mechanisms underlying the effects of acupuncture include neurohumors and neurotransmitters, which are involved in analgesia. At spinal level, Spinal opioids, glutamate, norepinephrine and serotonin are the key elements acupuncture-induced analgesia. At brain level, Endogenous opioid peptides, limbic system play essential roles in mediating the analgesia. Conclusion: Acupuncture is an effective approach to pain management. There is good evidence in both experimental and clinical research that supports acupuncture efficacy in management of chronic pain through central nervous system. Acupuncture should be strongly used as a part of pain management plans. This work helps in improving our understanding of the scientific basis underlying acupuncture analgesia.